Modular systems for energy and fuel recovery and conversion - Shah, Yatish T. (Boca Raton, FL : CRC Press, 2020)
Modular Systems for Energy and Fuel Recovery and Conversion surveys the benefits of the modular approach in the front end of the energy industry. The book also outlines strategies for managing modular approaches for fossil, renewable, and nuclear energy resource recovery and conversion with the help of successful industrial examples. The book points out that while the modular approach is most applicable for distributed and small-scale energy systems, it is also often used for parts of large-scale centralized systems. With the help of successful industrial examples of modular approaches for energy and fuel recovery and conversion, the book points out the need for more balance between large-scale centralized systems and small-scale distributed systems to serve the energy needs of rural and isolated communities. Coal, oil, natural gas, hydrogen, biomass, waste, nuclear, geothermal solar, wind, and hydro energy are examined, showing that modular operations are very successfully used in all these components of the energy industry. Aimed at academic researchers and industry professionals, this book provides successful examples and analysis of the modular operation for energy and fuel recovery and conversion. It is also a reference for those who are engaged in the development of modular systems for energy and fuel recovery and conversion.
1. Introduction 2. Modular Systems in Coal Industry 3. Modular Systems in Oil Industry 4. Modular Systems in Natural Gas and Hydrogen Industries 5. Modular Approaches in Biomass and Waste Industries 6. Modular Nuclear Reactors 7. Modular Wind Energy Systems 8. Modular Solar Energy Systems 9. Modular Geothermal Energy Recovery and Conversion 10. Modular Hydro Energy Systems
OCLC-licensed vendor bibliographic record.
Keywords: Small power production facilities; Power resources; Energy facilities; Fuel